Understanding Decisions to Suspend Works: When Employers Do Not Pay - Lee, Chia Kuang (EDP Sciences, 2018)
The construction industry propels Malaysia’s economic growth. Payment is the livelihood of the construction industry. Many contractors have suffered badly from payment issues in Malaysia, especially non-payment. To remedy non-payment, unpaid contractors have the right to suspend works if the construction contracts express such rights. However, this self-help remedy is less to be instigated and the reasons remained under explored. The aims of this paper are threefold: (1) to understand contractors’ reluctance to suspend works, (2) to predict contractors’ decision to suspend works from the lens of Theory of Planned Behaviour (TPB) model, and (3) to propose intervention strategies based on Institutional Theory. 44 Contractors specializing in building and civil engineering works participated in this study. The results show that Perceived obligations to others and tolerance factor underpinned their reluctance. Step-wise regression analysis also shows that subjective norm is the predictor of intention. To intervene in the decisions effectively, the TPB model was further extended with isomorphic pressures: Normative, Mimetic, and Coercive Pressures by drawing on Institutional Theory. These isomorphic pressures could be useful in influencing intention through subjective norm. The outcome of study is beneficial for both project practitioners and researchers, especially in improving payment issues in the Malaysian construction industry. Suspension of work can be seen as one of an effective self-help remedy that can be intervened in a macro framework.